2011
DOI: 10.1111/j.1525-1594.2011.01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mild Metabolic Acidosis on Cardiac Contractility and Isoprenaline Response in Isolated Ovine Myocardium

Abstract: The postoperative course after major surgical procedures such as cardiothoracic operations is often accompanied by acute metabolic abnormalities due to large volume and temperature shifts. In general, those intervention-induced trauma might cause the use of catecholamines to stabilize hemodynamics. Within the cardiac community, there are still controversial discussions about standardized medical therapy to treat postoperative acidosis, for example, buffering versus nonbuffering for improving catecholaminergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Recently, we showed that an acute mild metabolic pH shift to 7.20 did not influence cardiac contractility in the isolated trabeculae of nonfailing ovine hearts [24]. The results of the current study with end-stage human failing myocardium show a significant decrease in force amplitude under comparable conditions.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Recently, we showed that an acute mild metabolic pH shift to 7.20 did not influence cardiac contractility in the isolated trabeculae of nonfailing ovine hearts [24]. The results of the current study with end-stage human failing myocardium show a significant decrease in force amplitude under comparable conditions.…”
Section: Discussionsupporting
confidence: 53%
“…As previously described, the trabeculae were superfused with a HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) buffering solution, pH 7.40 (m M : NaCl 116, KCl 5, NaH 2 PO 4 2, MgCl 2 1.2, Na 2 SO 4 1.2, NaHCO 3 20, glucose 10, CaCl 2 initially at 0.25 and after with a stepwise increase of 2.0), at a temperature of 37°C and oxygenated with 100% O 2 [24]. Contractions were caused by electrical field stimulation (baseline, 1 Hz; 5 to 7 mV; STIM1, Scientific Instruments).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, the force of isolated human cardiac trabeculae increases ~81–168% as the stimulation frequency is increased from 0.5 Hz to 2.5 Hz (Chaudhary, et al, 2004; Pieske, et al, 1996; Rossman, et al, 2004). Increasing stimulation frequency in sheep trabeculae from 0.5 Hz to 2 Hz resulted in a 139–171% increase in force production (Schotola, et al, 2011; Sossalla, et al, 2010). Although, further increasing stimulation frequency to 3 Hz resulted in force decline.…”
Section: Sheep Modelsmentioning
confidence: 99%
“…Hanna Schotola et al. (92) of the University Hospital Goettingen, Goettingen, Germany investigated the influence of mild (and thus clinically relevant) acidosis on myocardial contractility and catecholamine response in explanted trabeculae of healthy ovine hearts. Two groups (group 1: pH = 7.40, n = 9 and group 2: pH = 7.20, n = 13) were studied, and force amplitudes were measured at frequencies between 30 and 180 beats per minute and increasing catecholamine concentrations (isoprenaline 0‐3 × 10(−6) mM).…”
Section: Cardiovascular Supportmentioning
confidence: 99%